Research and validation of forest carbon sequestration measurement model based on biomass method-A case study of Guizhou Province - Zhang Min; Wu Yang; Qiu Yan; Yan Jun; Li Chunling; Ran Wen Rui (PLoS ONE, 2025)
With the establishment of China Certified Voluntary Emission Reduction (CCER) market, more and more people pay attention to the development of forestry carbon sequestration in Guizhou. Guizhou is rich in forestry resources, but at the current stage, there are a series of measurement difficulties in the development of forestry carbon sequestration. Some traditional research methods have the problems of heavy workload and over-reliance on manual work. In view of the above problems, this paper studies the construction of carbon sequestration measurement model based on biomass estimation model. In this paper, sampling design, project boundary, carbon pool selection and other factors are considered in the construction of the model. At the same time, in view of the problem that the calculation results of the actual net carbon sequestration caused by CH4, N2O and other gas emissions in forestry carbon sequestration projects are not accurate enough, this study deduces a specific calculation model based on the actual project development needs and the data of 10 forest farms that have formed forestry carbon tickets. Taking Chinese fir as the research object, the effect of carbon sequestration model was verified and analyzed. Compared with the existing forestry carbon sequestration project evaluation, the results showed that the average relative error of the model was 6. 09%, and the absolute error range was 0. 348-4. 262/hm2, and the model effect was good. The establishment of the model not only solves the problems of over-reliance on manpower, material resources and inefficiency in the development of forestry carbon sequestration in China, but also accelerates the rapid and vigorous growth of forestry carbon sequestration industry in Guizhou, and contributes China's wisdom and effective solutions to global climate governance.